Effect of a Complex Plant Additive on Flour Mixes and Wheat Dough - Alexander V. Maslov; Zamira Sh. Mingaleeva; Timur A. Yamashev; Nailya F. Shibaeva (Техника и технология пищевых производств)
Food additives from non-traditional plant raw materials are a promising source of new fortified bakery products. However, they can affect the protein-starch structure of wheat flour and the rheological profile of the semi-finished bakery products, thus changing the quality of the finished product. The research objective was to study the effect of a novel plant food additive on the moisture, water absorption, and protein-proteinase complex of flour mixes and the rheological properties of wheat dough. The study featured flour mixes of top-grade wheat flour and the new food complex additive (10, 16, and 22%), as well as dough semi-finished products. The food complex additive consisted of whole grain wheat flour and powders of germinated spelt, pumpkin seeds, oyster mushrooms, and gooseberries in a ratio of 56.3:25.0:17.2:0.9:0.6, respectively. The moisture content was determined by the gravimetric method, while the water absorption and rheological properties were described using a Farinograph-AT. The content of wet gluten was measured by washing, the content of dry gluten was determined by drying, and the quality of gluten was tested according using an IDK-3M device. The additive decreased the water absorption and the dough development time, contributed to the gluten relaxation, and increased the amount and humidity of wet gluten. At 16 and 22% of the additive, the amount of dry gluten decreased by 3.4 and 4.0%, respectively; at 10%, it increased by 3.3%. The best stability, dough softening degree, and farinograph quality indicator were observed at 16%. The results can be used to produce new bakery products fortified with the new complex plant food additive, with the amount of water and kneading time adjusted for each particular case. Further research will feature the effect of the additive on the properties of dough semi-finished products during fermentation and proofing.